Improving Student's Learning Outcomes of The Third-Grade Students in Sdn 97 Pekanbaru on Landforms in Pekanbaru Topic Through Project Based Learning with Culturally Responsive Teaching Approach - Ramadianti, Ulfa Sari; Khairani, Suci Hadi; Mailizar, Betti; Mulyani, Eva Astuti; Yeni, Azimar; Syafril (Program Studi Pendididikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2025)
This research is a type of classroom action research that aims to improve student learning outcomes through the use of Project Based Learning with a Culturally Responsive Teaching approach on the subject of Landscape in Pekanbaru City. The subjects in this study were 30 students of class III B SDN 97 Pekanbaru. The results of the observation showed that the students' achievement was below the KKTP, caused by the lack of student enthusiasm and the delivery of material without clear visualization in class. The data collection techniques in this study were observation, documentation, and tests. The study was conducted in three stages, namely pre-cycle, cycle I, and cycle II. The results of the study showed an increase in each cycle with a large percentage of success in cycle II of 89.83%. Therefore, it can be concluded that the use of Project Based Learning with a Culturally Responsive Teaching approach can improve learning outcomes in the subject of science on the subject of landscape in Pekanbaru City class III B SDN 97 Pekanbaru